Revised Peck’s formula for estimating pipeline’s settlement under the coupling effect of tunnelling and vehicle load - Peng, Shu (Frontiers in Built Environment, 2025)
When the pipelines are subjected to shallow tunnel underpassing and ground traffic loads, the void effect will significantly amplify the dynamic response and safety risks of pipelines. A three-dimensional finite element model was established to quantify the adverse impact of tunnelling and vehicle load coupling. Then, based on the settlement distribution characteristics, a revised Peck formula is established to estimate the pipelines’ settlement in different depths and positions. The results reveal that the settlement of soil and pipeline caused by tunnelling decreases with decreasing burial depth; the dynamic settlement of the sewage pipe and ground surface is decreasing rapidly as the burial depth increases. Whether the pipeline is buried close to the surface or tunnel, it should be noted that the pipeline’s dynamic settlement or cumulative settlement may exceed the safety limit, and the safety risks of pipelines will be greatly underestimated by ignoring the dynamic settlement and its adverse impacts on the pipeline joints. When the depth is less than 1.5 m or the distance apart from the tunnel arch is less than 1.0 m, the pipelines’ settlement would exceed the limit.